2016
DOI: 10.18052/www.scipress.com/ilns.52.43
|View full text |Cite
|
Sign up to set email alerts
|

Short Review on the Aggressive Behaviour: Genetical, Biological Aspects and Oxytocin Relevance

Abstract: Abstract.In this mini-review we were interested in describing the main genetic, biological and mechanistic aspects of the aggressive behaviour in human patients and animal models. It seems that violent behaviour and impulsive traits present a multifactorial substrate, which is determined by genetic and non-genetic factors. Thus, aggressivity is regulated by brain regions such as the amygdala, which controls neural circuits for triggering defensive, aggressive or avoidant behaviour. Moreover, other brain struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…Besides its well-known role in reproduction [62] , oxytocin plays a significant role in most of the neuropsychiatric dysfunctions, with increased number of reports discussing especially the intranasal oxytocin management approach in disorders such as autism [63] , schizophrenia [64] , fronto-temporal dementia [65] , Prader Willi syndrome [66] , anxiety [67] , depression [68] , aggression [69] or suicide-related behavior [70] .…”
Section: Oxytocin Relevancementioning
confidence: 99%
“…Besides its well-known role in reproduction [62] , oxytocin plays a significant role in most of the neuropsychiatric dysfunctions, with increased number of reports discussing especially the intranasal oxytocin management approach in disorders such as autism [63] , schizophrenia [64] , fronto-temporal dementia [65] , Prader Willi syndrome [66] , anxiety [67] , depression [68] , aggression [69] or suicide-related behavior [70] .…”
Section: Oxytocin Relevancementioning
confidence: 99%
“…Violence is a multidimensional phenomenon produced through various isolated or simultaneous behaviors (Jevtic et al, 2014; Padurariu et al, 2016; Berlanda et al, 2019), which can operate at one or more different levels from the physical to the emotional, psychological and relational. Whereas physical aggression involves the infliction of physical harm, relational aggression is typically characterized by verbal abuse (e.g., shouting and screaming), spreading rumors, and exclusionary behaviors (Lansford et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors also found correlations between aggressive/violent behavior and oxytocin levels only in female suicide attempters (we would like to insist immediately on the relevance of this aspect). In fact, our research group also described earlier the complex interaction between aggressive behavior and oxytocin activities [45].…”
Section: Oxytocin Relevancementioning
confidence: 56%
“…We should also mention that the relationship between serotonin and aggressiveness [45] is an important aspect in studying the neurobiological underpinnings of suicide, especially in violent suicide cases. In fact, suicidal behavior is influenced by many biological variables that modify the serotonergic neurotransmission, including the psychosocial stress, traumatic experiences, pathological personality traits, disorders, or the alcohol abuse [46,47].…”
Section: Neurophysiological Mechanistics and Theories Of Suicidementioning
confidence: 99%
See 1 more Smart Citation